A proibição é sempre um final trágico: atuação censória na obra de Cassandra Rios (1975-1979) - Silva, Francisca Aline Cordeiro da (2024)
Having as objective the analysis the censorship against books during the dictatorial regime established in 1964, this research aimed to examine the way the books written by Cassandra Rios were received by the state (1932-2002), specifically focusing on the establishment of bans on her works. Cassandra Rios, pseudonyms used by Odete Rios, was born in São Paulo city and had her first book published on 1948 at the age of 16 years old. “A volúpia do Pecado” was a bestseller, and the first of 50 books she would eventually publish. As she had her work launched e relaunched amidst a military dictatorship (1964-1985), and her writings predominantly portrayed lesbian characters and depicted explicit sexual practices, her productions did not escape the scrutiny of the censorship eyes. Approximately 36 of her books were banned, and our study focused on 13 censorship processes the resulted in the prohibition of her books, sush as: A volúpia do pecado, A sarjeta, A paranoiac, Copacabana posto 6, Georgette, A borboleta branca, A breve estória de Fábia, Uma mulher diferente, Tessa, a gata, Veneno, Nicoleta ninfeta, Marcella e As traças, documentation available at the National Archives of the Federal District. Engaging with scholars such as Marcelino (2006), Lucas (2017; 2020), and Vieira (2016), we explored Rios's integration into the publishing market during the 1970s and the role of censorship during that period. Our analysis reveals that the rationale behind the prohibitions, although grounded in the preservation of 'good morals,' involved censorship focusing on aspects such as character development, the message conveyed, and the presence of death as a means of influencing readers.